Overshooting Americanisation. Accent Stylisation in Pop Singing – Acoustic Properties of the Bath and Trap Vowels in Focus - Konert-Panek, Monika (Research in Language, 2017)
The paper addresses the problem of overshoot involved in singing accent stylisation. Selected phonetic features indexed as “American” and “Cockney” are analysed in the singing and speaking styles of a British vocalist, Adele. Overshoot, understood as a greater frequency or an exaggerated quality of a given feature, is characteristic of staged performance (Bell and Gibson 2011; Coupland 2007). PRAAT is used to establish the acoustic properties (F1 and F2) of the BATH and TRAP vowels, as well as the presence or absence of the BATH-TRAP split. The results show that Americanisation regarding the BATH-TRAP split in singing is present and the Americanised vowel tokens are “overshot”, having higher F2 frequency compared with the regular British TRAP vowel.